2015
DOI: 10.1016/j.febslet.2015.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and development of local inhibitory and excitatory neurons associated with dopaminergic nuclei

Abstract: Edited by Wilhelm JustKeywords: Dopamine GABA Glutamate Substantia nigra Ventral tegmental area Rostromedial tegmental nucleus a b s t r a c t For regulation of voluntary movement and motivation the midbrain dopaminergic system receives input from a variety of brain regions. Often this input is mediated by local non-dopaminergic neurons within or closely associated with the dopaminergic nuclei. In addition to the dopaminergic neurons, some of these non-dopaminergic neurons also send functionally important outp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 131 publications
(209 reference statements)
0
19
0
Order By: Relevance
“…Thus, we next investigated the cellular composition of DAC3.0 MOs. We found that both GABAergic and mDA neurons are intimately colocated in most of the rosettes (Figure A), like in midbrain, where GABAergic neurons closely interact with mDA neurons in the substantia nigra, ventral tegmental area, and rostromedial tegmental nucleus . In contrast, DAC0 MOs (0 μM CHIR99021) and NS‐MOs (0.8 μM CHIR99021) exhibited heterogeneous distribution of GABAergic neurons.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Thus, we next investigated the cellular composition of DAC3.0 MOs. We found that both GABAergic and mDA neurons are intimately colocated in most of the rosettes (Figure A), like in midbrain, where GABAergic neurons closely interact with mDA neurons in the substantia nigra, ventral tegmental area, and rostromedial tegmental nucleus . In contrast, DAC0 MOs (0 μM CHIR99021) and NS‐MOs (0.8 μM CHIR99021) exhibited heterogeneous distribution of GABAergic neurons.…”
Section: Resultsmentioning
confidence: 80%
“…Midbrain contains not only mDA neurons, a functional cell type representative of the midbrain, but also several other cell types, such as different neuronal subtypes, astrocytes, and oligodendrocytes, which exert roles in maintaining the functional homeostasis of the midbrain . Thus, we next investigated the cellular composition of DAC3.0 MOs.…”
Section: Resultsmentioning
confidence: 99%
“…Function of these monoaminergic pathways is controlled by inhibitory and excitatory neurons, including important populations residing locally within the monoaminergic nuclei as well as in the adjacent midbrain and anterior hindbrain (Russo and Nestler, 2013;Lammel et al, 2014;Proulx et al, 2014;Morello and Partanen, 2015). Dysfunction of monoaminergic circuits is thought to lead to a multitude of psychiatric and neurophysiological disorders, such as schizophrenia, depression, addiction and Parkinson's disease.…”
Section: Introductionmentioning
confidence: 99%
“…For α-HBCD, glutamate significantly decreased following mid- and high-dose exposures. The contribution of glutamate to synaptic transmission, plasticity, and development is well established (Morello and Partanen 2015). For γ-HBCD, phenylalanine decreased significantly in both γ-HBCD dose groups.…”
Section: Discussionmentioning
confidence: 99%